UPAR+ extracellular vesicles: a robust biomarker of resistance to checkpoint inhibitor immunotherapy in metastatic melanoma patients. Issue 5 (10th May 2021) - Porcelli, Letizia; Guida, Michele; De Summa, Simona; Di Fonte, Roberta; De Risi, Ivana; Garofoli, Marianna; Caputo, Mariapia; Negri, Antonio; Strippoli, Sabino; Serratì, Simona; Azzariti, Amalia
Abstract : Background: Emerging evidence has highlighted the importance of extracellular vesicle (EV)-based biomarkers of resistance to immunotherapy with checkpoint inhibitors in metastatic melanoma. Considering the tumor-promoting implications of urokinase-type plasminogen activator receptor (uPAR) signaling, this study aimed to assess uPAR expression in the plasma-derived EVs of patients with metastatic melanoma to determine its potential correlation with clinical outcomes. Methods: Blood samples from 71 patients with metastatic melanoma were collected before initiating immunotherapy. Tumor-derived and immune cell-derived EVs were isolated and analyzed to assess the relative percentage of uPAR + EVs. The associations between uPAR and clinical outcomes, sex, BRAF status, baseline lactate dehydrogenase levels and number of metastatic sites were assessed. Results: Responders had a significantly lower percentage of tumor-derived, dendritic cell (DC)-derived and CD8 + T cell-derived uPAR +EVs at baseline than non-responders. The Kaplan-Meier survival curves for the uPAR + EV quartiles indicated that higher levels of melanoma-derived uPAR + EVs were strongly correlated with poorer progression-free survival (p<0.0001) and overall survival (p<0.0001). We also found a statistically significant correlation between lower levels of uPAR + EVs from both CD8 + T cells and DCs and better survival. Conclusions: Our results indicate that higher levels of tumor-derived, DC-derived and CD8 + T cell-derived uPAR + EVs in non-responders may represent a new biomarker of innate resistance to immunotherapy with checkpoint inhibitors. Moreover, uPAR + EVs represent a new potential target for future therapeutic approaches.